2021
DOI: 10.3390/ani11123530
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Alopecia and Thyroid Atrophy in Sheep

Abstract: Thyroid dysfunction substantially affects the quality of life due to its association with various disorders in different organs. A low intake of selenium and zinc can predispose to thyroid alterations, resulting in hypothyroidism. A deficiency of selenium and zinc causes direct and indirect skin lesions, both by the action of free radicals on the skin and by thyroid dysfunction. The aim of this study was to describe natural cases of diffuse alopecia and thyroid abnormalities in sheep with selenium and zinc def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In a recent study from Brazil concluded that severe alopecia and fibrosis and atrophy with thyroid deficiency is associated with zinc and selenium deficiency in sheep. The researchers also noticed that deficiency of these two elements is associated with hypothyroidism and that addition of zinc and selenium improve thyroid function both in animals and humans [11].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study from Brazil concluded that severe alopecia and fibrosis and atrophy with thyroid deficiency is associated with zinc and selenium deficiency in sheep. The researchers also noticed that deficiency of these two elements is associated with hypothyroidism and that addition of zinc and selenium improve thyroid function both in animals and humans [11].…”
Section: Methodsmentioning
confidence: 99%
“…Thus for this, a lack of selenium-induced liver circulation disorders or immune stress are also associated with heart failure and downregulation of splenic cell proliferation ( 25 , 26 ). In addition, selenium can indirectly cause thyroid atrophy, alopecia, and keratosis in goats by affecting the activation of macrophages in the liver ( 27 ). Mechanically, researcher found that the protective effects of selenium on liver are possibly attributed to the upregulation of antioxidant enzyme activity in macrophages and the inhibition of inflammatory factor secretion ( 28 ).…”
mentioning
confidence: 99%